ANALISIS KEPUASAN PELAYANAN PUSKESMAS TERHADAP PASIEN BPJS DAN NON BPJS MENGGUNAKAN METODE SERVQUAL - Utami Mizani Putri (LPPM STMIK Lombok, 2021)
E-puskesmas is a government work program in the health sector which is expected to be able to assist the puskesmas in Palembang in fulfilling the need for daily service records ranging from patient data, medical records, medicines and many more. E-puskesmas is also a strategy that can be used to prevent loss of customers (patients) by creating customer loyalty through quality service. To determine the quality of health services from the Puskesmas towards the services received, one of them is by using the Service Quality (servqual) method. The sampling method used was simple random sampling technique so that 192 respondents were obtained, consisting of 174 respondents for BPJS patients and 18 respondents for Non-BPJS patients with 21 statement attributes. The results obtained for CSI are 80% for BPJS patients and for Non-BPJS patients by 77% which is between 66% - 80.99% which means that patients are satisfied with the performance of e-puskesmas services, then for the servqual method the difference is generated (Gap) of 0.16 for BPJS patients and for Non BPJS patients the difference (Gap) is 0.61. All the results of the servqual value are positive, which indicates that the services available at the e-puskesmas have met patient satisfaction.